Cognitive Moral Based on Civics Education Material in Elementary School - Yogi Prihandoko; St. Y. Slamet; Winarno Winarno (Intelektual Pustaka Media Utama, 2018)
This study aims to determine the effectiveness of the use of cognitive moral based on civics education teaching material in improving the moral judgement competence of the fifth grade elementary school students. This study is a quasi experiment using pretest-postest control group design. The subjects were 59 students of the fifth grade elementary school consisting of 31 students of experimental class and 28 students of control class. The treatment of the experimental class used cognitive moral based on civics education teaching material for about 8 weeks. Learning process in the control class is on the same material and time intensity, but they were not given a treatment. Technique of collecting data used is test. The test instrument consists of 25 multiple choice questions dominated by a moral dilemma. The result of independent sample t test shows that t value is higher than t table (2.161 more than 1.671). The results show that cognitive based civics education teaching material is effective in improving the moral judgement competence of the fifth grade elementary school students. The increasing moral judgement competence in the experimental class based on the acquisition score N-Gain 0.36 is the medium category.